T cell activation is determined by the number of presented antigens. - Deeg, J; Axmann, M; Matic, J; Liapis, A; Depoil, D; Afrose, J; Curado, S; Dustin, M; Spatz, J (2013)
Antigen recognition is a key event during T cell activation. Here, we introduce nanopatterned antigen arrays that mimic the antigen presenting cell surface during T cell activation. The assessment of activation related events revealed the requirement of a minimal density of 90-140 stimulating major histocompatibility complex class II proteins (pMHC) molecules per μm(2). We demonstrate that these substrates induce T cell responses in a pMHC dose-dependent manner and that the number of presented pMHCs dominates over local pMHC density.